Pemdampingan Untuk Mempermudah Belajar Arti Al-Qur’an Melalui Qur’any 2 Di TPQ Al – Firdaus Bareng Jombang - Ali Mustofa; Nurul Indana; Afta Zita Hasro; Alifah Ayu Setyaningsih; Baiq Elistiana Ulfa; Ita Nurmalasari; Nazilatur Rohmah; Siti Saira Mochsen; Susi Kurniawati; Wilanti Ahmad (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2023)
In education, the learning process and the use of methods are very influential for children's learning outcomes. Learning the Qur'an is not only learning to read and write it, but also in understanding the meanings of the words in the Qur'an. The methods that can be used in learning the Qur'an are very diverse. One method that is easy and fast is the method with the Qur'any system. The method with the Qur'any system is a method of learning the Koran easily and quickly with the teaching principle of 2 x 3. In this service the method used is the PAR (Participatory Action Research) research approach. PAR is a participatory research and development method that recognizes the social connections and values ??of the reality of our experiences, thoughts and feelings. The initial step taken was to provide teaching assistance while observing and analyzing conditions. The second step is to start implementing assistance in learning the meaning of the Qur'an through Qur'any 2. The next third step is to carry out an evaluation.